2007
DOI: 10.1016/j.labeco.2005.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Market conditions and worker training: How does it affect and whom?

Abstract: This paper analyses the impact of labor market conditions on a firm's incentive to train its workers. In an equilibrium model of the labor market in which firms use both untrained and inhouse-trained workers, we show that the incidence of training increases with the tightness of the labor market. In a multi-sector framework, the usual threat of hold-up by a trained worker is more severe for workers who change their sector of work; during downturns, this serves to bias firms' incentives in imparting training aw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 14 publications
(18 reference statements)
1
18
0
Order By: Relevance
“…17 Our hypothesis is that in times of a tight labor market, firms relying on hiring workers from the external labor market face more difficulties satisfying their labor demand than training firms, and are therefore inclined to train workers internally. Askilden and Nilsen (2005), Majumdar (2007), Wolter et al (2006) and Muehlemann et al (2007) previously found that firms operating in a tight labor market are more likely to train apprentices. 15 Note that 1 − α − β is equal to the fraction of time the apprentice spends at the workplace that has no direct productive value to the firm.…”
Section: Econometric Modelingmentioning
confidence: 91%
“…17 Our hypothesis is that in times of a tight labor market, firms relying on hiring workers from the external labor market face more difficulties satisfying their labor demand than training firms, and are therefore inclined to train workers internally. Askilden and Nilsen (2005), Majumdar (2007), Wolter et al (2006) and Muehlemann et al (2007) previously found that firms operating in a tight labor market are more likely to train apprentices. 15 Note that 1 − α − β is equal to the fraction of time the apprentice spends at the workplace that has no direct productive value to the firm.…”
Section: Econometric Modelingmentioning
confidence: 91%
“…Based on data from the US National Longitudinal Survey of Youth (NLSY), Majumdar (2007) Felstead et al (2012) find that the crisis had not a dramatic negative impact on training provision. Only a minority of establishments reduced spending per head.…”
Section: Previous Empirical Evidencementioning
confidence: 99%
“…There is empirical evidence for training being counter-cyclical (Sepulveda, 2004) or pro-cyclical Bassanini and Brunello, 2008;Majumdar, 2007). However, all studies that have analysed the effects of the Great Recession find negative effects on establishments' training activities (Bellmann et al, 2014;Felstead et al, 2012;Mason and Bishop, 2015;Popov, 2014).…”
Section: Hypothesesmentioning
confidence: 99%
“…The few studies on the impact of a recession on further training lead to contradicting results. Based on data from the US National Longitudinal Survey of Youth (NLSY), Majumdar (2007) reveals pro-cyclical training activities for the period from 1979 to 1988. He shows that the probability of receiving training decreases with the local unemployment rate.…”
Section: Previous Empirical Evidencementioning
confidence: 99%